The contribution of the geography of disability to the development of ‘accessible tourism’ - Zajadacz, Alina (Turyzm/Tourism, 2015)
The article presents an outline of the evolution of the geography of disability (since the 1930s) taking into account significant issues in the creation of theoretical foundations as well as practical action in ‘accessible tourism’. It may be considered a review. Based on an analysis of literature, the first section presents a definition of ‘accessible tourism’ and the development of the geography of disability, the result of which is the geographical model of disability. The second section is a synthetic presentation of the effect of geographical research on the development of theoretical accessible tourism concepts and their implications in practice. The final conclusions highlight the need to identify the level of detail in universal design principles applied to buildings, spaces, services, which are to fulfil the criteria of accessibility for people with various types of disability.